Dissecting the molecular interactions between botanical extracts and the human gut microbiota - Mancabelli, Leonardo; Tarracchini, Chiara; Longhi, Giulia; Alessandri, Giulia; Ventura, Marco; Turroni, Francesca (Frontiers in Microbiology, 2025)
Over millions of years, humans and their gut microbes have developed a symbiotic relationship that benefits both organisms. Many plants and herbs consumed as food by humans, such as aloe vera gel and dandelion root extracts, contain bioactive compounds with recognized therapeutic or preventive effects. However, the impact of these botanicals on the composition and functionality of the human gut microbiota is not yet understood. In this study, the molecular impact of these botanicals on reconstructed human gut microbiota was assessed by in-vitro bioreactor experiments followed by metagenomics and transcriptomic approaches, highlighting both taxonomic and functional changes in the human gut microbiome. Furthermore, cross-feeding activities established by common human gut microbial taxa like Bacteroides spp. when cultivated on these extracts were assessed. In conclusion, the results show that botanicals affect intestinal populations that are highly dependent on the microbial taxa present and that trophic interactions are established in few key gut members.